THE FEMINISM PORTRAYED IN GRETA GERWIG’S MOVIE LITTLE WOMEN; ANALYSIS IN MODERN ERA - Nurmala Dewi; Tatia Ishlah Medina (English Study Program University of Pasir Pengaraian, 2021)
This paper discussed feminism in the Little Women movie directed by Greta Gerwig in 2019. This movie is adapted from Louisa May Alcott’s novel which was written initially in 1868. This study aimed to find out how feminism is described through the leading character. The other objective is to search the types of feminism on main character refers to Tong and Botts’s theory. The writer used descriptive qualitative methods which content analysis of the movie. All data is presented in the form of words and sentences and used library research as a way to collect data by reading and selecting quotations from the Little Women movie. As the result, it is found that there are five types of feminism: Liberal Feminism type, Marxist Feminism and Socialist type, Radical libertarian Feminism type, Psychoanalytic Feminism type, and Postmodern Feminism type. Besides the types of feminism, the discussions depicted feminism impact to the characters among women and sends the views and values in women personal life with connected to the relationship of family matters as well.